Why is Malaria still a critical issue? A systematic review in Asia particularly in Indonesia - Wekadigunawan, Cri Sajjana Prajna; Rabbani, Ananda Farrell (Journal of Language and Health, 2025)
Malaria continues to be an important public health concern across many Asian nations, with Indonesia remaining one of the most affected country. Despite significant advancements in diagnostics, treatment, and vector control strategies, multiple challenges hinder Indonesia's goal of malaria elimination by 2030. This systematic review describes the epidemiological burden of malaria in Asia with a focus on Indonesia, outlines key challenges such as geographical, ecological, and socio-cultural-political barriers, and discusses comprehensive strategies to overcome these obstacles. A systematic literature search was conducted through electronic databases such as PubMed and Google Scholar, as well as official reports from the World Health Organization (WHO) and the Ministry of Health of the Republic of Indonesia (Kemenkes RI), using keywords like ‘malaria’, ‘Indonesia’, ‘elimination’, ‘malaria challenges’ and ‘vector management’. The selection criteria prioritized scientific publication and official reports published between 2011 and 2025 to ensure the currency of the data. Strengthening surveillance, community empowerment, regional and cross-border cooperation, and innovation in control tools are essential to achieving malaria elimination in Indonesia and other endemic countries in Asia.